THE APPLICATION OF LOCAL AND INTEGRATED THEORIES OF MUAVRLAPLAS TO SOME ISSUES - G`affarova Dilfuza Shavkat qizi; Narzullayeva O`g`iloy Bahrom qizi (Journals Park Publishing, 2023)
In this article, we will examine the practice of Muavr-Laplas, one of the main theories of Probability Theory, on some issues of the nest of local and integrated theories.
Keywords: Probability, phenomenon, Bernulli formula, local and integrated theories of Muavr-Laplas.